Assessing the effectiveness of flipped classroom strategies in enhancing nursing student engagement and knowledge retention - Shrestha, S; Shrestha, N; Acharya, S (Devdaha Medical Journal, 2026)
Introduction: The flipped classroom teaching learning method has been increasingly adopted in higher education to enhance student centered learning. Despite its growing popularity, limited evidence exists regarding its effectiveness in nursing education in Nepal. Nursing education requires innovative teaching strategies to develop critical thinking, clinical competence, and active engagement. Traditional lectures often lead to passive learning, low retention, and limited application in practice. This study aimed to examine the effectiveness of flipped classroom strategies, compared to traditional lecture-based learning, in improving engagement, knowledge retention, and learning experiences among undergraduate nursing students at Devdaha Medical College and Research Institute. Methods: A mixed-methods quasi-experimental study was conducted among 40 first-year undergraduate nursing students at Devdaha Medical College and Research Institute, Nepal. Students were purposively assigned to an intervention group (flipped classroom) and a control group (traditional lecture). Knowledge outcomes were assessed through pre, post, and delayed-tests, while student engagement was measured using a Likert scale survey and student learning experiences was evaluated through focus group discussions. Quantitative data were analyzed using descriptive statistics, t-tests, and effect sizes. Qualitative data were thematically analyzed and triangulated with quantitative results. Results: Both groups demonstrated significant improvements in knowledge scores from pre- to post-test. However, the flipped classroom group achieved greater knowledge gains (mean difference = 3.65, Cohen’s d = 1.20) compared to the control group (mean difference = 2.20, Cohen’s d = 0.79). Delayed-test results confirmed superior retention in the flipped classroom group. Engagement surveys revealed high behavioral, emotional, and cognitive involvement, with mean scores ranging from 4.27 to 4.47 out of 5. Thematic analysis highlighted benefits such as enhanced preparation, active participation, collaboration, and confidence in applying knowledge to clinical practice. Conclusion: Flipped classroom strategies significantly enhanced knowledge retention, engagement, and confidence among nursing students. Although quantitative engagement differences were modest, qualitative data revealed substantial perceived benefits. Flipped learning is recommended in nursing curricula, with attention to time management and resource accessibility.